Development of Podcast-Based Learning Media for Analyzing Fictional Works in Grade VIII at SMP Negeri 1 Sitiung - Salahuddin, Amar; Aprimadedi, Aprimadedi; Fadillah, Nur (The Future of Education Journal, 2025)
This study aims to develop podcast-based learning media on the material of reviewing works of fiction for grade VIII students at SMPN 1 Sitiung. This research uses the Research and Development (R&D) method with the 4D development model, which includes the Define, Design, Develop, and Disseminate stages. This research was conducted at SMPN 1 Sitiung in the 2024/2025 school year with the research subjects being class VIII students totaling 32 people. Data collection techniques were carried out through student and teacher response questionnaires, as well as validation sheets involving media experts, material experts, and linguistic experts. The results of this study show that researchers produce podcast-based learning media as a learning medium for material to determine the elements of short stories, the media is said to be valid, seen from the results of media expert validation obtained a score of 93.75% and included the “very valid” category, material expert validation obtained a score of 71.43% including the ‘valid’ category, linguistic expert validation obtained a score of 89.28% including the “very valid” category. This means that learning media is suitable for use by educators and students. The results of the practicality assessment conducted by educators obtained a score of 86.36% including the category “very valid” and VIII grade students obtained a score of 81.25% including the category “very valid”.